2007
DOI: 10.1111/j.1365-2567.2007.02654.x
|View full text |Cite
|
Sign up to set email alerts
|

Over‐expression of the bovine FcRn in the mammary gland results in increased IgG levels in both milk and serum of transgenic mice

Abstract: SummaryThe neonatal Fc receptor (FcRn) protects immunoglobulin G (IgG) from catabolism and is also responsible for IgG absorption in the neonatal small intestine. However, whether it mediates the transfer of IgG from plasma to milk still remains speculative. In the present study, we have generated transgenic mice that over-express the bovine FcRn (bFcRn) in their lactating mammary glands. Significantly increased IgG levels were observed in the sera and milk from transgenic animals, suggesting that the over-exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
44
2

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(54 citation statements)
references
References 38 publications
(59 reference statements)
8
44
2
Order By: Relevance
“…Although it is difficult to ascribe exactly the contribution of the hemopoietic cell population to IgG homeostasis, the bone marrow chimera experiments demonstrate that it plays a significant role, at a level that is potentially similar to the role of endothelial cells. FcRn expressed at other sites may also extend the half-life of serum IgG as suggested for FcRn expressed in the mammary gland (45). Taken together, however, our results suggested that bone marrow-derived cells and vascular endothelial cells are major cell types responsible for the FcRn-dependent extension of serum IgG half-life.…”
Section: Discussioncontrasting
confidence: 50%
“…Although it is difficult to ascribe exactly the contribution of the hemopoietic cell population to IgG homeostasis, the bone marrow chimera experiments demonstrate that it plays a significant role, at a level that is potentially similar to the role of endothelial cells. FcRn expressed at other sites may also extend the half-life of serum IgG as suggested for FcRn expressed in the mammary gland (45). Taken together, however, our results suggested that bone marrow-derived cells and vascular endothelial cells are major cell types responsible for the FcRn-dependent extension of serum IgG half-life.…”
Section: Discussioncontrasting
confidence: 50%
“…Increasing the FcRn expression by transgenesis to reduce IgG clearance is yet an unexplored approach for improving hyperimmunization. We and others have recently shown that higher than normal expressional level of FcRn reduced exogenous IgG catabolism (11,14,34).…”
Section: Discussionmentioning
confidence: 84%
“…The mechanism was originally thought to be mediated mainly by endothelial cells, which line blood vessels (8). However, recent findings suggest that this process occurs also in hematopoietic cells (9,10), or even in mammary epithelial cells during lactation (11).…”
mentioning
confidence: 99%
“…The development of the mammary glands and deposition/accumulation of IgG in colostrum late in pregnancy (Lu et al, 2007) could also represent an extravascular sink for IgG, possibly contributing to the observed third trimester and postpartum V d changes (Table 2). It is noteworthy that these hemodynamic changes in the rat model could mimic human changes (Dowell and Kauer, 1997), suggesting that mAb V d and Cls changes may also occur during human pregnancy.…”
Section: Changing Mab Pharmacokinetics Across Rat Reproductive Cycle 419mentioning
confidence: 99%